Electrosorption of cadmium and arsenic from wastewaters using nitrogen-doped biochar: Mechanism and application. (1st January 2022) - Lin, Shiwei; Yang, Xiong; Liu, Lihu; Li, Anyu; Qiu, Guohong
Abstract: Biochar has been widely applied as an adsorbent, whose electrochemical capacity and heavy metal adsorption performance can be improved by nitrogen doping. In this work, nitrogen-doped biochar (NBC) was synthesized by calcinating sodium humate with sodium bicarbonate (NaHCO3 ) and urea as the activation agent and nitrogen source, respectively. The NBC was then used to electrochemically adsorb Cd(II) and As(III, V) from simulated and actual wastewaters, respectively. The results indicated that NaHCO3 activation and nitrogen doping could increase the surface area and nitrogen content of the biochar, contributing to the enhancement of adsorption performance for Cd(II) and As(III, V). The electrosorption capacities for Cd(II) and total arsenic (As(T)) increased first and then reached equilibrium with increasing nitrogen content, increased first and then decreased with increasing calcination temperature, and consistently increased with increasing voltage. The Cd(II) electrosorption capacity (79.0 mg g −1 ) and As(T) removal ratio (94.0%) at 1.2 V in actual As-contaminated wastewater (1.16 mg L −1 ) were about 4 and 2.6 folds of their inorganic adsorption capacities, respectively. After five cycles of reuse, the Cd(II) and As(T) removal ratio could be maintained at 65.8% and 51.7% of the initial electrosorption capacity. This work expands the application of NBC for heavy metal removal. Graphical abstract: Image 1 Highlights: N-doped biochar shows larger surface area and well-developed pore structure. N doping obviously improves the electrosorption capacity of biochar for Cd and As. The removal capacity of N-doped biochar for Cd(II) reaches 79.0 mg g −1 . The As(T) removal ratio using N-doped biochar is 94.0% from actual wastewaters.